قلق الذات وهاجس الموت في مرحلة الشيخوخة: قصيدة "سبعون" لعبدالعزيز الرفاعي نموذجا - المقيم، طارق بن محمد (جامعة الأميرة نورة بنت عبد الرحمن, 2023)
تأتي هذه الدراسة لتكشف عن أسباب استحسان النقاد لقصيدة "سبعون" للشاعر عبدالعزيز الرفاعي، ومدى قدرته على إيصال تجربة قلقه من هاجس الموت، حيث ظهرت أعراض عدة تدل على ذلك القلق، منها: الرجوع إلى الماضي واستلهامه، والتهويل مما لاقاه من زمنه، والشكوى من كافة أمور حياته، وارتباط أجزاء القصيدة كافة بموضوع القلق. واستطاع الشاعر أن يستعين ببعض الحيل النفسية والتوافقية لتجاوز "هاجس الموت" من خلال استعانته بالأصدقاء، واستدعاء الكتاب ليجعله عوضا عما فقده من أصحاب وملذات الحياة الأخرى، ليصل لدرجة الرضا والاستسلام في آخر المطاف. وأجاد الشاعر في نقل مشاعره بدقة، من خلال وسائل فنية عدة كالموسيقا الخارجية التي ناسبت الموضوع، والصور الفنية المركبة والمترابطة، كما حرص أن يقدم كلمات كان من حقها التأخير، لدلالتها على قلقه وصراعه النفسي دون تكلف من خلال اعتماده على لغة الفن واللاشعور. This study comes to reveal the reasons for the critics' approval of the "sabaun" poem by Abdulaziz Al-Rifai, and the extent of the poet's ability to communicate his experience of death anxiety and the conflict that the self faced with him, and the poet used several methods and strategies for that, such as returning to the past and, and exaggeration of what he found from his time And the large number of complaints about all matters of his life, and the subject of concern was what united the meanings of the poem and made it revolve around it. The poet was able to use some psychological and consensual tricks to overcome the "anxiety of death" through his use of friends, and when he missed them he called the book to make it instead of what he lost from other friends and pleasures of life, to reach the point of contentment and surrender in the end. Just as the poet was able to accurately convey his feelings, he did it by conveying it in an artistic way through an external music that matched the subject, as well as through multiple and interlinked artistic images, as he was keen to present words that were entitled to delay due to their indication of his anxiety and psychological struggle without cost by relying on the language of art And subconscious.
Keywords: الشعر العربي -- قلق الذات -- مرحلة الشيخوخة -- الرفاعي، عبدالعزيز بن أحمد، 1993 م